Web engineering 12th international conference, ICWE 2012, Berlin, Germany, July 23-27, 2012. proceedings - Tokuda, Takehiro; Tolksdorf, Robert; Brambilla, Marco (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 12th International Conference on Web Engineering, ICWE 2012, held in Berlin, Germany, in July 2012. The 20 revised full papers and 15 short papers were carefully reviewed and selected from 98 submissions. The papers are organized in topical sections on social networks and collaboration, tagging, personalization and personal systems, search, Web modeling, AJAX and user interfaces, Web services, Web crawling, and Web and linked data management. The book also includes 6 poster papers, 12 demos and 5 tutorials.